Community-Based Lodging: A Local Economy Catalyst and Tourist Interaction on Lemukutan Island, West Kalimantan Province - Marini, Marini; Nisak, Cut Lusi Chairun; Amsi, Al Mujaddidah Hidayah; Puspitasari, Helen (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the influence of community-based lodging on the local economy on Lemukutan Island, focusing on the extent to which these lodgings can serve as catalysts for local economic growth and strengthen interactions between tourists. The method is qualitative, with in-depth interviews with inn managers, local communities, and tourists. The study results show that community-based lodging has a significant positive impact on the local economy, including job creation, increased demand for local products, and collaboration with other economic sectors such as transportation and tourism activities. In addition, this inn also introduces local products such as handicrafts and speciality foods to tourists, ultimately increasing local business actors' income. The study also identifies the challenges faced, such as the limitations of infrastructure and human resource skills in the tourism sector, which need to be overcome through training and collaboration with related parties. The opportunity for community-based lodging development is immense, given the growing interest of tourists in getting an immersive, authentic experience. In conclusion, community-based lodging on Lemukutan Island has great potential to support local economic empowerment. Still, it requires infrastructure improvements, human resource training, and better marketing strategies to expand its positive impact.